(untitled) (ACME, 2014)
The Theban tomb (TT) 31 of Khonsu, First Prophet of Menkheperre, is an ideal casestudy to understand the perception of natural and constructed landscapes, throughout the analysis of their different iconographies. Starting from the description of the decorative programme of Khonsu’s tomb, it could be possible to identify elements of continuity and differences between the depictions of the different sacred structures that can be appreciated also within the Theban and Amarnian tombs of the nobles during the XVIII and XIX Dynasty. The use of specific themes and iconographies might correspond to peculiar conceptions of the most sacred space, the temple.